Educación intercultural y teatro: un aporte desde la experiencia peruana - Rodrigo Benza Guerra; Fidel Tubino Arias Schreiber (Universidade Federal do Norte do Tocantins, 2021)
Interculturality, in our context, is determined by the relations between indigenous populations and the hegemonic culture implemented after the European conquest. In this sense, intercultural education arises mainly oriented to the rural indigenous population and is marked by the need to reclaim and revitalize displaced and marginalized cultures. It is important, however, to understand that relations of discrimination go back and forth and that is why it is necessary to make a proposal for intercultural education that considers not only the indigenous population, but also the members of the hegemonic culture. In this text we seek to problematize the approach to intercultural education and propose, based on three practical experiences of intercultural theater in the Peruvian Amazon, that the methodology of theater, due to its particular characteristics: development of play, generating a dialogue between reality and fiction, valuing the body, recognizing the importance of the sensitive, promoting diverse languages, among others, can help in the construction of the diverse objectives of intercultural education.